Queen of hearts - Jones, Jasmine (New York : Disney Press, 2006)
Raven's boyfriend Devon may be moving away if his father remarries, so Raven attempts to stop the wedding so she can convince Devon's father that she and Devon are meant to be together.
"Based on the television series, "That's So Raven," created by Michael Poryes and Susan Sherman."
"Part one is based on the episode written by Sarah Jane Cunningham & Suzie V. Freeman. Part two is based on the episode written by Sarah Jane Cunningham & Suzie V. Freeman."
"From the hit TV series on Disney Channel"--Cover.
Keywords: African Americans -- Juvenile fiction; Families -- Juvenile fiction; Weddings -- Juvenile fiction